Perceived barriers and benefits of Intervention on Health Beliefs about Drugs of High School’s Female Students - Mohammed, Saja Mahdi; Sadoon, Hajar Haider; Mohammed, Israa Dhyaa (Central Asian Journal of Medical and Natural Science, 2025)
This investigation sought to explore the effects of a belief-based intervention regarding health on the prevention of drugs in female students in Diwaniyah. Additionally, it sought to determine the association between preventative strategies for drugs and the demographic characteristics of female students, such as age, grade, economic status of the family, and atmosphere in the family. This research utilized a true experimental design and a randomized controlled trial methodology to determine if an intervention based on the health belief model would have an effect on the beliefs of addiction to drugs among high school students in Diwaniyah, CA between January 7th, 2025 and May 15th, 2025. The results demonstrated that the concept of health belief was different in the context of drug prevention. The study concluded that the health intervention via the health belief model had a positive impact on female students’ health beliefs and emphasizes the need to prevent drug use. According to the study, further research based on the HBM should be conducted on a large segment of the Iraqi community in order to alter drug consumption..